Evaluation of in situ technique for predicting ruminal protein degradation - Burguer, Peter Johann; Bonnecarrére Sanchez, Luis Maria; Pires, Maria Beatriz Gonçalves; Zannella, Irineo (Pesquisa Agropecuaria Brasileira, 2014)
This work was carried out from September 1985 to February 1986, at the Animal Nutrition Laboratory of the Animal Science Department of the Universidade Federal de Santa Maria, in Santa Maria, RS, Brazil. Two Frisian cows with ruminal fistula, maintained indoors on a lucerne (Medicago sativa L.) hay ad libitum diet were used for the experiment. The nitrogen (N) disappearance from food samples placed in nylon bags at the rumen was estimated with the in situ technique. The used substrata were soybean meal (Glycine max (L.) Merrill), meat meal, lucerne hay, and napier grass (Pennisetum purpureum Schum.) in five fermentation times: 1, 3, 6, 12 and 24 hours during three consecutive days of the assay. The experimental design used was the split-split-plot in blocks with two replications. There were no significant differences (P < 0,05) between animals and replicates. However, high differences between days of assay, substrata, interaction of days vs. substrata, and substrata vs. fermentation times were observed (P < 0,01). It was concluded that the in situ technique proved to be repeatable and accurate, with low variation coefficient (5,22%). The necessity of standardization, quantification and control of variation factors was emphasised.